Internationalization of Al-Ittifaqiah Islamic Boarding School Indralaya, Ogan Ilir, South Sumatra - Rosidah, Umi; Maftuhah, Maftuhah; Tobroni , Tobroni; Faridi , Faridi (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2025)
This study aims to examine the internationalization efforts carried out by Pesantren Al Ittifaqiah, including aspects of the curriculum, collaboration with international institutions, and development of the competence of students and educators. The research method used is a qualitative approach with data collection through interviews, observations, and documentation. The results of the study show that Pesantren Al Ittifaqiah has integrated a traditional Islamic based curriculum with international education programs, such as teaching foreign languages (Arabic and English) and organizing student exchange programs abroad. In addition, this pesantren also collaborates with various international educational institutions to develop academic programs and improve the capacity of educators. The internationalization of this pesantren has a positive impact on improving the quality of students, especially in terms of language skills, global insight, and academic competence. However, this process also faces various challenges, such as limited facilities, the need to adapt to global culture, and limited funding. This study concludes that the internationalization of Islamic boarding schools not only strengthens the position of Al Ittifaqiah Islamic Boarding School in the national Islamic education arena, but also opens up opportunities for students to compete at the global level without losing their Islamic identity.